Implementasi Tenaga Kerja dengan Perjanjian Kerja Berdasarkan Peraturan Daerah Surakarta Nomor 2 Tahun 2023 Tentang Pengelolaan Jasa - Kushandi, Eusthacia Arzeti; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2025)
This research aims to find out a clear picture of the systematic implementation of the procurement of TKPK services, obstacles and strategies to overcome obstacles regarding the procurement of labor services with employment agreements in Surakarta City. This type of research includes descriptive research. The research approaches taken are: statute approach, case approach, historical approach, and conceptual approach. The main data collection techniques were conducted through interviews and library data collection. The results of the research include: 1) The rationale for the issuance of Surakarta Mayor Regulation number 37 of 2021 concerning Guidelines for Procurement of Labor Services with Employment Agreements is in accordance with the needs of services to the community. The implementation of Labor Procurement with Employment Agreements in Surakarta City has been carried out in accordance with the support of the PDIP faction of the Surakarta City DPRD and the Personnel and Human Resources Development Agency carries out tasks related to planning, implementation and evaluation of TKPK in Surakarta City. 2). There are several obstacles that arise in the implementation of TKPK in Surakarta City. These are found in: Regulations and Policies are considered less consistent. Local Labor Empowerment is considered less appropriate. Evaluation and continuous improvement are not implemented. Budget Management and Performance Management System. 3) The strategy implemented to overcome the obstacles in the implementation of TKPK procurement in Surakarta City is that the strategy of Clarifying Regulations and Policies consistently, managing the Budget well and collaborating with other parties as a source of TKPK budget. Through the implementation of consistent clarification of regulations and policies, good budget management, and cooperation with other parties as a source of budget for TKPK employees. Suggestions that can be outlined are that future researchers with the same subject matter should further expand the scope of discussion related to problem-sol